Reversible Bronchiectasis in COVID-19 Survivors With Acute Respiratory Distress Syndrome: Pseudobronchiectasis - Hu, Qiongjie; Liu, Yiwen; Chen, Chong; Sun, Ziyan; Wang, Yujin; Xiang, Min; Guan, Hanxiong; Xia, Liming (Frontiers in Medicine, 2021)
To retrospectively analyze whether traction bronchiectasis was reversible in coronavirus disease 2019 (COVID-19) survivors with acute respiratory distress syndrome (ARDS) and whether CT findings were associated with the reversibility, 41 COVID-19 survivors with ARDS were followed up for more than four months. Demographics, clinical data, and all chest CT images were collected. The follow-up CT images were compared with the previous CT scans. Twenty-eight (68%) patients with traction bronchiectasis (Group I) and 13 (32%) patients without traction bronchiectasis (Group II) on CT images. Traction bronchiectasis disappeared completely in 21 of 28 (75%) patients (Group IA), but did not completely disappear in 7 of 28 (25%) patients (Group IB). In the second week after onset, the evaluation score on CT images in Group I was significantly higher than that in Group II (p=0.001). The proportion of reticulation on the last CT images in Group IB was found higher than that in Group IA (p < 0.05). COVID-19 survivors with ARDS might develop traction bronchiectasis, which can be absorbed completely in most patients. Traction bronchiectasis in a few patients did not disappear completely, but bronchiectasis was significantly relieved. The long-term follow-up is necessary to further assess whether traction bronchiectasis represents irreversible fibrosis.